Crystal structure of (glycinto-κ 2 O,N ′)-[5,5,7,12,12,14-hexamethyl-1,4,8,11-tetraazacyclotetradecane-κ 4 N,N ′,N ″,N ‴]nickel(II) perchlorate monohydrate C18H42ClN5NiO7 - Zhang Zu-Jiao; Ou Guang-Chuan (Zeitschrift für Kristallographie - New Crystal Structures, 2023)
C18H42ClN5NiO7, orthorhombic, Pca21 (no. 29), a = 14.270(3) Å, b = 9.918(2) Å, c = 17.603(4) Å, V = 2491.4(10) Å3, Z = 4, R gt(F) = 0.0382, wR ref(F 2) = 0.0861, T = 173(2) K.